Zika virus in rhesus macaque semen and reproductive tract tissues: a pilot study of acute infection. Issue 5 (6th August 2020) - Schmidt, Jenna K; Mean, Katherine D; Puntney, Riley C; Alexander, Eric S; Sullivan, Ruth; Simmons, Heather A; Zeng, Xiankun; Weiler, Andrea M; Friedrich, Thomas C; Golos, Thaddeus G
Abstract: Although sexual transmission of Zika virus (ZIKV) is well-documented, the viral reservoir(s) in the male reproductive tract remains uncertain in humans and immune-intact animal models. We evaluated the presence of ZIKV in a rhesus macaque pilot study to determine persistence in semen, assess the impact of infection on sperm functional characteristics, and define the viral reservoir in the male reproductive tract. Five adult male rhesus monkeys were inoculated with 10 5 PFU of Asian-lineage ZIKV isolate PRVABC59, and two males were inoculated with the same dose of African-lineage ZIKV DAKAR41524. Viremia and viral RNA (vRNA) shedding in semen were monitored, and a cohort of animals were necropsied for tissue collection to assess tissue vRNA burden and histopathology. All animals exhibited viremia for limited periods (1–11 days); duration of shedding did not differ significantly between viral isolates. There were sporadic low levels of vRNA in the semen from some, but not all animals. Viral RNA levels in reproductive tract tissues were also modest and present in the epididymis in three of five cases, one case in the vas deferens, but not detected in testis, seminal vesicles or prostate. ZIKV infection did not impact semen motility parameters as assessed by computer-assisted sperm analysis. Despite some evidence of prolonged ZIKV RNA shedding in human semen and high tropism of ZIKV for male reproductive tract tissues in mice deficient in Type 1 interferon signaling, in the rhesus macaques assessed in this pilot study, we did not consistently find ZIKV RNA in the male reproductive tract. Abstract : Male rhesus monkeys, evaluated 1–6 weeks following subcutaneous Zika virus inoculation, have sporadic presence of viral RNA in the epididymis and semen.